The New Age of Terrorism and the International Political System - Guelke, Adrian (London I.B.Tauris, 2010)
Did the 9/11 attacks on the US usher in a new age of mass-casualty terrorism and war on terrorist groups of a global reach? This title questions whether terrorism has evolved into a new form of political violence or whether it remains essentially unchanged.
INclude Index and Bibliography
Keywords: Terrorism -- Political violence -- September 11 Terrorist Attacks (2001)